Preparation method of high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material
By introducing chopped carbon fibers and MAS phases into SiBCN ceramic matrix composites, a high-temperature ablation-resistant SiBCN-MAS composite materials were prepared, which solved the problem of poor ablation resistance of existing SiBCN ceramic matrix composites and achieved better high-temperature mechanical properties and oxidation resistance.
Patent Information
- Application Number
- CN202310984549.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-08-07
AI Technical Summary
The existing SiBCN ceramic matrix composite materials have poor ablation resistance at high temperatures, and the bonding force between carbon fiber and SiBCN ceramic contact surface is poor.
The preparation method of chopped carbon fiber reinforced SiBCN-MAS composite material is adopted to prepare cracked carbon coated chopped carbon fiber and SiBCN amorphous ceramic powder, and introduce the MAS phase, and improve the binding force between the fiber and the matrix through ultrasonic oscillation and ball milling and wet mixing.
It significantly improves the high-temperature ablation resistance of SiBCN ceramic matrix composite materials, reduces the mass ablation rate and linear ablation rate, and improves the mechanical characteristics and oxidation resistance of the material.
Smart Images

Figure CN116969774B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a SiBCN ceramic-based composite material. Background Art
[0002] When a spacecraft is flying at high speed, its surface will be subjected to severe aerodynamic thermal effects, resulting in various problems such as rapid temperature rise and ablation. In this process, the material undergoes a series of physical and chemical changes such as phase change, melting, decomposition, vaporization, oxidation, mechanical erosion, corrosion, and microstructural changes. Among all these properties, ablation resistance is the most critical. Because it is directly related to the ablation morphology, structural component thickness, aerodynamic shape, etc. of the surface of the spacecraft material; at the same time, the surface of the material will produce amazing heat and mass loss under rapid cooling and heating and high-temperature hot air flow, resulting in a gradual decline in its performance and even structural failure, which in turn affects the safety of the entire space mission. SiBCN ceramic materials have a unique high-temperature structure, and the atoms inside the material are mainly covalent bonds, which ensures that the material can maintain a long-range disordered and short-range ordered morphology at around 1500°C, showing excellent high-temperature mechanical properties, oxidation resistance and creep resistance. Among them, the SiBCN nano-scale amorphous ceramic powder prepared by mechanical alloying is low-cost, environmentally friendly, and can be mass-produced. It is prepared at low temperature, simple to operate, has a short process cycle, and is easy to design a process flow. However, for MA-SiBCN materials (SiBCN materials prepared by mechanical alloying) with low self-diffusion coefficients, the powder components cannot achieve uniform density during the sintering process. In addition, the mass ablation rate and line ablation rate of pure SiBCN ceramics are 20.796 mg / s and 0.047 mm / s, respectively. Therefore, the problem of poor high-temperature ablation resistance of existing SiBCN ceramics still cannot guarantee the safety and reliability of the material in actual service environments.
[0003] The density and ablation resistance of SiBCN ceramic-based composites can be enhanced by carbon fibers or cracked carbon-coated carbon fibers, but the bonding strength between the two contact surfaces is poor and the improvement in high-temperature ablation resistance is limited. Summary of the invention
[0004] The present invention aims to solve the problems that the existing carbon fiber or cracked carbon coated carbon fiber reinforced SiBCN ceramic matrix composites have poor contact bonding strength and limited improvement in high temperature ablation resistance, and further provides a method for preparing a high temperature ablation resistant chopped carbon fiber reinforced SiBCN-MAS composite material.
[0005] A method for preparing a high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material is carried out according to the following steps:
[0006] 1. Preparation of pyrolysis carbon coated chopped carbon fibers:
[0007] The short carbon fibers are placed in an acetone solution of a phenolic resin and mixed, and after mixing, taken out, dried, and subjected to cracking treatment to obtain short carbon fibers with cracked carbon coatings;
[0008] 2. Preparation of SiBCN amorphous ceramic powder:
[0009] Ball-milling graphite powder, hexagonal boron nitride powder and silicon powder to obtain SiBCN amorphous ceramic powder;
[0010] 3. Mixed raw materials:
[0011] The SiBCN amorphous ceramic powder, the MAS phase, the short carbon fiber with the cracked carbon coating and the anhydrous ethanol are wet-mixed by ball milling, ultrasonically vibrated and dried after mixing to obtain a mixed raw material;
[0012] The MAS phase is composed of MgO, Al2O3 and SiO2, and the molar ratio of MgO to Al2O3 is 1:(1-2); the molar ratio of MgO to SiO2 is 1:(2-3);
[0013] 4. Sintering:
[0014] The mixed raw materials are pre-pressed into a shape and then sintered in a nitrogen atmosphere to obtain a high-temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite material.
[0015] The beneficial effects of the present invention are:
[0016] The purpose of the present invention is to improve the bonding force between the contact surface of carbon fiber and SiBCN ceramic, and to introduce MAS phase to enhance the anti-ablation performance of existing carbon fiber or cracked carbon coated carbon fiber reinforced SiBCN ceramic matrix composite material.
[0017] During the sintering process, MAS can significantly improve the melting characteristics of SiBCN ceramics, and can effectively prevent the crystallization of SiBCN, accelerate its grain formation in the matrix, and reduce the melting temperature, thereby improving the mechanical properties of SiBCN ceramics. MAS and ceramics are combined to make up for the shortcomings of their respective performances; carbon fiber has good mechanical properties and is an ideal material for preparing SiBCN ceramic composites, but for carbon fiber toughened ceramic-based composites, their mechanical properties not only depend on the properties of the matrix and carbon fiber, but also are affected by the bonding characteristics of the fiber and the matrix. Too strong or too weak the bonding strength between the fiber and the matrix will seriously affect the reinforcement and toughening effect of the fiber. Appropriate fiber-matrix bonding is required so that it will not suffer catastrophic damage when subjected to external forces and crack expansion, while also being able to maintain its original performance advantages.
[0018] The process method of the present invention is simple and the preparation process cycle is short. The short carbon fibers modified by the cracked carbon interface are prepared by introducing the MAS phase and the impregnation cracking method, which reduces the sintering difficulty and improves the inert bonding force between the fiber and the SiBCN ceramic matrix contact surface. Compared with the existing carbon fiber or cracked carbon coated carbon fiber reinforced SiBCN ceramic matrix composite material, the high temperature ablation resistance is improved. Taking the SiBCN ceramic matrix composite material with 6wt.% MAS and 5vol.% cracked carbon coated short carbon fiber content as an example, the minimum mass ablation rate is 0.013g / s. Taking the SiBCN ceramic matrix composite material with 6wt.% MAS and 10vol.% cracked carbon coated short carbon fiber content as an example, the minimum linear ablation rate is 0.037mm / s, which gives the SiBCN ceramic good high temperature ablation resistance.
[0019] Instruction Manual
[0020] Figure 1 The present invention is a flow chart for preparing the high temperature ablation resistant chopped carbon fiber reinforced SiBCN-MAS composite material;
[0021] Figure 2 The XRD spectrum of the SiBCN amorphous ceramic powder prepared in step 2 of Example 1;
[0022] Figure 3 is the TG-DTA diagram of the phenolic resin described in Example 1;
[0023] Figure 4 This is a surface morphology of the chopped carbon fiber with a cracked carbon coating prepared in step 1 of Example 1;
[0024] Figure 5 The mechanical properties test diagram of the high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material prepared in Examples 1 to 4;
[0025] Figure 6 The fracture morphology of the high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite materials prepared in Examples 1 to 4, (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4;
[0026] Figure 7 The surface temperature of the high temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite material prepared in Examples 1 to 4 changes with time after ablation;
[0027] Figure 8 This is a comparison chart of the mass ablation rate and the line ablation rate of the high-temperature ablation-resistant chopped carbon fiber reinforced SiBCN-MAS composite material after ablation prepared in Examples 1 to 4. DETAILED DESCRIPTION
[0028] Specific implementation method 1: Combination Figure 1 Specifically, this embodiment is a method for preparing a high temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite material, which is carried out according to the following steps:
[0029] 1. Preparation of pyrolysis carbon coated chopped carbon fibers:
[0030] The short carbon fibers are placed in an acetone solution of a phenolic resin and mixed, and after mixing, taken out, dried, and subjected to cracking treatment to obtain short carbon fibers with cracked carbon coatings;
[0031] 2. Preparation of SiBCN amorphous ceramic powder:
[0032] Ball-milling graphite powder, hexagonal boron nitride powder and silicon powder to obtain SiBCN amorphous ceramic powder;
[0033] 3. Mixed raw materials:
[0034] The SiBCN amorphous ceramic powder, the MAS phase, the short carbon fiber with the cracked carbon coating and the anhydrous ethanol are wet-mixed by ball milling, ultrasonically vibrated and dried after mixing to obtain a mixed raw material;
[0035] The MAS phase is composed of MgO, Al2O3 and SiO2, and the molar ratio of MgO to Al2O3 is 1:(1-2); the molar ratio of MgO to SiO2 is 1:(2-3);
[0036] 4. Sintering:
[0037] The mixed raw materials are pre-pressed into a shape and then sintered in a nitrogen atmosphere to obtain a high-temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite material.
[0038] The beneficial effects of this embodiment are:
[0039] The purpose of this embodiment is to improve the bonding force between the contact surface of carbon fiber and SiBCN ceramic, and to introduce the MAS phase to enhance the ablation resistance of the existing carbon fiber or cracked carbon coated carbon fiber reinforced SiBCN ceramic matrix composite material.
[0040] During the sintering process, MAS can significantly improve the melting characteristics of SiBCN ceramics, and can effectively prevent the crystallization of SiBCN, accelerate its grain formation in the matrix, and reduce the melting temperature, thereby improving the mechanical properties of SiBCN ceramics. MAS and ceramics are combined to make up for the shortcomings of their respective performances; carbon fiber has good mechanical properties and is an ideal material for preparing SiBCN ceramic composites, but for carbon fiber toughened ceramic-based composites, their mechanical properties not only depend on the properties of the matrix and carbon fiber, but also are affected by the bonding characteristics of the fiber and the matrix. Too strong or too weak the bonding strength between the fiber and the matrix will seriously affect the reinforcement and toughening effect of the fiber. Appropriate fiber-matrix bonding is required so that it will not suffer catastrophic damage when subjected to external forces and crack expansion, while also being able to maintain its original performance advantages.
[0041] The process method of this embodiment is simple and the preparation process cycle is short. By introducing the MAS phase and the impregnation pyrolysis method to prepare pyrolysis carbon interface modified chopped carbon fibers, the sintering difficulty is reduced and the inert bonding force between the fiber and the SiBCN ceramic matrix contact surface is improved. Compared with the existing carbon fiber or pyrolysis carbon coated carbon fiber reinforced SiBCN ceramic matrix composites, the high temperature ablation resistance is enhanced and improved. Taking the SiBCN ceramic matrix composite with 6wt.% MAS and 5vol.% pyrolysis carbon coated chopped carbon fiber content as an example, it has a minimum mass ablation rate of 0.013g / s. Taking the SiBCN ceramic matrix composite with 6wt.% MAS and 10vol.% pyrolysis carbon coated chopped carbon fiber content as an example, it has a minimum linear ablation rate of 0.037mm / s, which gives the SiBCN ceramic good high temperature ablation resistance.
[0042] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the chopped carbon fiber described in step 1 is the chopped carbon fiber after degumming, and the degumming is carried out according to the following steps: the chopped carbon fiber is placed in an acetone solution for ultrasonic vibration for 10 minutes to 30 minutes, and finally filtered out with a sieve and dried naturally. The rest is the same as specific embodiment 1.
[0043] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the concentration of the phenolic resin in the acetone solution of the phenolic resin in step 1 is 30 g / L to 50 g / L. The rest is the same as specific implementation method 1 or 2.
[0044] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: in step 1, short-cut carbon fibers are placed in an acetone solution of phenolic resin, and ultrasonically shaken and stirred for 10 min to 30 min under the conditions of an ultrasonic power of 400 W to 600 W and a stirring speed of 150 rpm to 300 rpm, and then filtered out with a sieve and dried naturally, and then heated to 700 ℃ to 900 ℃ at a heating rate of 5 ℃ / min to 15 ℃ / min in a nitrogen atmosphere, and kept warm for 30 min to 60 min at a temperature of 700 ℃ to 900 ℃. Others are the same as specific embodiments 1 to 3.
[0045] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the length of the chopped carbon fiber described in step 1 is 1.5 mm to 3 mm, the diameter is 6 μm to 8 μm, and the density is 1.7 g / cm 3~ 1.9g / cm 3 The rest is the same as the specific implementation modes 1 to 4.
[0046] Specific implementation method 6: This implementation method is different from the specific implementation methods 1 to 5 in that: in step 2, graphite powder, hexagonal boron nitride powder and silicon powder are placed in a high-energy ball milling tank, ball milled under argon atmosphere, ball-to-material ratio of (15-30):1 and rotation speed of 500rpm-800rpm, and the ball milling is suspended for 10min-40min every 0.4h-1h during the ball milling process, the effective ball milling time is 20h-40h, and the ball milling is passed through a 100-mesh 150-mesh sieve after ball milling; the molar ratio of the graphite powder to the hexagonal boron nitride powder is 3:(1-2); the molar ratio of the graphite powder to the silicon powder is 3:(1-2). Others are the same as the specific implementation methods 1 to 5.
[0047] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that the graphite powder particle size in step 2 is 5.0 μm to 10.0 μm, the hexagonal boron nitride powder particle size is 0.2 μm to 1 μm, and the silicon powder particle size is 5.0 μm to 10.0 μm. Others are the same as specific embodiments 1 to 6.
[0048] Specific embodiment eight: This embodiment differs from one of specific embodiments one to seven in that: Step three, at a rotation speed of 250rpm to 350rpm, the SiBCN amorphous ceramic powder, MAS phase, short carbon fiber with cracked carbon coating and anhydrous ethanol are ball-milled and wet-mixed for 8h to 12h, and then ultrasonically vibrated for 20min to 40min at an ultrasonic power of 400W to 600W, and finally the solvent is evaporated at a temperature of 80℃ to 100℃ to obtain a mixed raw material; the volume of the anhydrous ethanol and the total mass ratio of the SiBCN amorphous ceramic powder, MAS phase and short carbon fiber with cracked carbon coating is (3 to 5) mL: 1g. The rest is the same as specific embodiments one to seven.
[0049] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the mass percentage of the MAS phase in the mixed raw material described in step 3 is 3% to 10%; the volume percentage of the chopped carbon fibers with cracked carbon coating in the mixed raw material is 5% to 20%. Others are the same as specific embodiments 1 to 8.
[0050] Specific embodiment 10: This embodiment differs from the first to ninth embodiments in that: in step 4, the mixed raw material is pre-pressed for 10 min to 30 min under the condition of a pre-pressing pressure of 20 MPa to 30 MPa, and then the mixed raw material is pre-pressed in a nitrogen atmosphere with a vacuum degree of 0.9×10 -5 Pa~1.0×10 -5 Pa and a heating rate of 2°C / min to 5°C / min, the temperature was raised to 1600°C to 1800°C, and the temperature was kept at a nitrogen atmosphere and a vacuum of 0.9×10 -5 Pa~1.0×10 -5 Pa, sintering pressure of 50MPa-80MPa and temperature of 1600℃-1800℃, keep warm for 30min-60min, and cool to room temperature at a cooling rate of 2℃ / min-5℃ / min after sintering. Others are the same as the first to ninth embodiments.
[0051] The following examples are used to verify the beneficial effects of the present invention:
[0052] Embodiment 1:
[0053] A method for preparing a high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material is carried out according to the following steps:
[0054] 1. Preparation of pyrolysis carbon coated chopped carbon fibers:
[0055] The chopped carbon fibers were placed in an acetone solution of phenolic resin, and the mixture was stirred and mixed under ultrasonic vibration for 20 minutes at an ultrasonic power of 600 W and a stirring speed of 200 rpm. After mixing, the mixture was filtered out with a sieve and naturally dried for 36 hours. Then, the mixture was heated to 800°C at a heating rate of 10°C / min in a nitrogen atmosphere, and kept at 800°C for 30 minutes, and naturally cooled to room temperature to obtain chopped carbon fibers with a cracked carbon coating.
[0056] The concentration of phenolic resin in the acetone solution of phenolic resin is 50 g / L;
[0057] 2. Preparation of SiBCN amorphous ceramic powder:
[0058] Put graphite powder, hexagonal boron nitride powder and silicon powder into a high-energy ball mill, and ball mill under argon atmosphere, ball-to-material ratio of 20:1 and rotation speed of 600rpm. During the ball milling process, the ball milling is suspended for 40min for every 1h, and the effective ball milling time is 40h. After ball milling, the powder is passed through a 100-mesh sieve to obtain SiBCN amorphous ceramic powder; the molar ratio of graphite powder: hexagonal boron nitride powder: silicon powder is 3:1:2;
[0059] 3. Mixed raw materials:
[0060] At a rotation speed of 200 rpm, SiBCN amorphous ceramic powder, MAS phase, short carbon fiber with cracked carbon coating and anhydrous ethanol were ball-milled and wet-mixed for 10 hours, and then ultrasonically vibrated for 30 minutes at an ultrasonic power of 600 W, and finally the solvent was evaporated at a temperature of 100 ° C for 4 hours to obtain a mixed raw material;
[0061] The MAS phase is composed of MgO, Al2O3 and SiO2, and the molar ratio of MgO:Al2O3:SiO2 is 2:2:5;
[0062] The mass percentage of the MAS phase in the mixed raw material is 6%; the volume percentage of the chopped carbon fibers with cracked carbon coating in the mixed raw material is 5%; the total mass ratio of the volume of the anhydrous ethanol to the SiBCN amorphous ceramic powder, the MAS phase and the chopped carbon fibers with cracked carbon coating is 5mL:1g;
[0063] 4. Sintering:
[0064] The mixed raw materials were pre-pressed for 10 min under a pre-pressing pressure of 30 MPa, and then the mixture was pre-pressed in a nitrogen atmosphere with a vacuum degree of 1.0×10 -5 Pa and a heating rate of 2 °C / min, the temperature was raised to 1800 °C and the vacuum was 1.0 × 10 -5Under the conditions of 60MP Pa, sintering pressure of 60MP and temperature of 1800℃, the sintering was carried out for 60min, and the temperature was cooled to room temperature at a cooling rate of 3℃ / min after sintering to obtain high-temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite materials.
[0065] The chopped carbon fiber described in step 1 is the chopped carbon fiber after degumming treatment, and the degumming treatment is carried out according to the following steps: placing the chopped carbon fiber in an acetone solution for ultrasonic vibration for 20 minutes, and finally filtering it out with a sieve and drying it naturally.
[0066] The chopped carbon fiber described in step 1 has a length of 2 mm, a diameter of 7 μm, and a density of 1.8 g / cm 3 , tensile strength is 4900MPa, tensile modulus is 230GPa, and elongation is 2.1%.
[0067] The phenolic resin described in step 1 is a phenolic resin produced by Macklin;
[0068] The graphite powder described in step 2 has a purity of 99.5% and a particle size of 8.7 μm; the hexagonal boron nitride powder has a purity of 99.9% and a particle size of 0.6 μm; and the silicon powder has a purity of 99.99% and a particle size of 9.0 μm.
[0069] The high temperature ablation resistant chopped carbon fiber reinforced SiBCN-MAS composite material prepared in Example 1 has a pyrolysis carbon coating chopped carbon fiber content of 5.vol% and a volume density of 2.56g / cm 3 , porosity 2.2%, flexural strength 400.2MPa, hardness 6.2Gpa, fracture toughness 4.5MPa·m 1 / 2 . The size is φ30×5mm 2 The sample was subjected to oxyacetylene flame ablation test. The distance between the sample and the nozzle was 10 mm, the ablation time was 10 s, the mass ablation rate was 0.013 g / s, and the line ablation rate was 0.048 mm / s.
[0070] Embodiment 2: This embodiment is different from Embodiment 1 in that the volume percentage of the chopped carbon fibers with cracked carbon coating in the mixed raw material described in step 3 is 10%. Other aspects are the same as Embodiment 1.
[0071] The high temperature ablation resistant chopped carbon fiber reinforced SiBCN-MAS composite material prepared in Example 2 has a pyrolysis carbon coating chopped carbon fiber content of 10.vol% and a volume density of 2.52g / cm 3 , porosity 2.6%, flexural strength 334.8MPa, hardness 5.2Gpa, fracture toughness 4.0MPa·m 1 / 2 . The size is φ30×5mm 2The sample was subjected to oxyacetylene flame ablation test. The distance between the sample and the nozzle was 10 mm, the ablation time was 10 s, the mass ablation rate was 0.017 g / s, and the line ablation rate was 0.037 mm / s.
[0072] Embodiment 3: This embodiment is different from Embodiment 1 in that the volume percentage of the chopped carbon fibers with cracked carbon coating in the mixed raw material described in step 3 is 15%. The rest is the same as Embodiment 1.
[0073] The high temperature ablation resistant chopped carbon fiber reinforced SiBCN-MAS composite material prepared in Example 3 has a pyrolysis carbon coating chopped carbon fiber content of 15.vol% and a volume density of 2.44g / cm 3 , porosity 1.7%, flexural strength 287.2MPa, hardness 4.8Gpa, fracture toughness 3.3MPa·m 1 / 2 . The size is φ30×5mm 2 The sample was subjected to oxyacetylene flame ablation test. The distance between the sample and the nozzle was 10 mm, the ablation time was 10 s, the mass ablation rate was 0.016 g / s, and the line ablation rate was 0.052 mm / s.
[0074] Embodiment 4: This embodiment is different from Embodiment 1 in that the volume percentage of the chopped carbon fibers with cracked carbon coating in the mixed raw material described in step 3 is 20%. Other aspects are the same as those of Embodiment 1.
[0075] The high temperature ablation resistant chopped carbon fiber reinforced SiBCN-MAS composite material prepared in Example 4 has a pyrolysis carbon coating chopped carbon fiber content of 20.vol% and a volume density of 2.38g / cm 3 , porosity 3.1%, flexural strength 256.9MPa, hardness 4.2Gpa, fracture toughness 3.3MPa·m 1 / 2 . The size is φ30×5mm 2 The sample was subjected to oxyacetylene flame ablation test. The distance between the sample and the nozzle was 10 mm, the ablation time was 10 s, the mass ablation rate was 0.026 g / s, and the line ablation rate was 0.038 mm / s.
[0076] Bending strength test in Examples 1 to 4: the size of the sample is 20 mm×4 mm×3 mm (length×width×height), the test span is 16 mm, and the rate of the indenter loading is 0.5 mm / min;
[0077] Hardness test: The hardness tester load is increased to 49.09N and maintained for 5s;
[0078] Fracture toughness test: The dimensions are 20 mm × 4 mm × 20 mm (length × height × width), the lateral span is 16 mm, the incision depth is 2 mm, the incision width is about 0.2 mm, and the operating speed of the indenter is 0.05 mm / min.
[0079] Comparing with Examples 1 to 4, the bulk density gradually decreases with the increase of fiber content, reaching a minimum of 2.38 g / cm when 20 vol.% fiber is introduced. 3 .
[0080] Figure 2 This is the XRD spectrum of the SiBCN amorphous ceramic powder prepared in step 2 of Example 1; it can be seen from the figure that the prepared SiBCN powder has an amorphous structure.
[0081] Figure 3 This is the TG-DTA diagram of the phenolic resin described in Example 1; it can be seen from the figure that the pyrolysis temperature setting range should be 700°C to 900°C.
[0082] Figure 4 This is the surface morphology of the chopped carbon fiber with cracked carbon coating prepared in step 1 of Example 1; as can be seen from the figure, the phenolic resin impregnation solution will gradually form a continuous covering cracked carbon coating on the surface of the chopped carbon fiber. Since the thickness is not completely uniform and there are some protrusions on the surface, the specific surface area and roughness of the carbon fiber surface are increased, and the cracked carbon coating does not contain impurities.
[0083] Figure 5 The mechanical properties test diagram of the high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material prepared in Examples 1 to 4; it can be seen from the figure that the flexural strength, hardness and fracture toughness of the short carbon fiber reinforced SiBCN-MAS composite material gradually decrease with the increase of the introduced fiber content, among which when the carbon fiber content is 5 vol.%, the hardness, flexural strength and fracture toughness of the composite material are the highest, reaching 6.2 GPa, 400.2 MPa and 4.5 MPa·m respectively. 1 / 2 When the carbon fiber content is 20 vol.%, the porosity of the composite material is the largest, and its hardness and flexural strength are the lowest, which are 4.2 GPa, 256.9 MPa and 3.3 MPa·m 1 / 2 .
[0084] Figure 6The high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material prepared for Examples 1 to 4 is shown in the fracture morphology, (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4; it can be seen from the figure that the composite material has good coating performance, the fiber content exposed on its surface is low, and it has a high ceramic content and a large ceramic particle size. At the same time, it can be seen that the pores inside the material first decrease and then increase, but the rate of increase in the density of the material is significantly slowed down. Obviously, with the increase in fiber content, the content of SiBCN in the short carbon fiber reinforced SiBCN-MAS composite material is gradually reduced, while the pores are first reduced and then increased. Coating the carbon coating on the surface of the carbon fiber will not damage the surface and will improve the toughness of the composite material. The presence of the carbon coating indicates that there is a good mechanical bonding state between the matrix and the fiber, thereby improving the interface bonding between the carbon fiber and the matrix.
[0085] Figure 7 The surface temperature of the high temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite material prepared in Examples 1 to 4 after ablation changes with time; it can be seen from the figure that the maximum surface temperature of the samples in Examples 1 to 4 reached 2080°C, 2158°C, 2152°C and 2170°C respectively, and the surface temperature of the composite material rose rapidly from 5vol.% to 20vol.% to nearly 1500°C within 2 seconds at the beginning of heating, which shows the sudden temperature rise phenomenon of the sample after being suddenly sprayed with oxygen-acetylene flame. At the beginning of ablation, due to the large temperature gradient inside the sample, it may cause large thermal stress.
[0086] Figure 8 The comparison chart of mass ablation rate and linear ablation rate of the high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material after ablation prepared in Examples 1 to 4; it can be seen from the figure that the introduction of MAS phase and pyrolysis carbon interface modified short carbon fiber, the mass ablation rate and linear ablation rate of SiBCN ceramic matrix composite material after ablation change significantly, and has a certain degree of optimization and improvement effect on its ablation resistance. The SiBCN ceramic matrix composite material with 6wt.% MAS and 5vol.% pyrolysis carbon coated short carbon fiber content has the smallest mass ablation rate of 0.013g / s, and the SiBCN ceramic matrix composite material with 6wt.% MAS and 10vol.% pyrolysis carbon coated short carbon fiber content has the smallest linear ablation rate of 0.037mm / s.
Claims
1. A method for preparing a high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material, characterized in that It is carried out in the following steps:
1. Preparation of pyrolysis carbon coated chopped carbon fibers: The short-cut carbon fiber is placed in an acetone solution of phenolic resin, and the mixture is stirred and mixed for 10 min to 30 min under the conditions of ultrasonic power of 400 W to 600 W and stirring speed of 150 rpm to 300 rpm, and filtered out with a sieve after mixing and naturally dried, and then heated to 700° C. to 900° C. at a heating rate of 5° C. / min to 15° C. / min in a nitrogen atmosphere, and kept at 700° C. to 900° C. for 30 min to 60 min to obtain the short-cut carbon fiber with pyrolysis carbon coating; The concentration of the phenolic resin in the acetone solution of the phenolic resin is 30 g / L to 50 g / L; The length of the chopped carbon fiber is 1.5 mm to 3 mm, the diameter is 6 μm to 8 μm, and the density is 1.7 g / cm 3~ 1.9g / cm 3 ; 2. Preparation of SiBCN amorphous ceramic powder: Put graphite powder, hexagonal boron nitride powder and silicon powder into a high-energy ball mill, and ball mill them under the conditions of argon atmosphere, ball-to-material ratio of (15-30):1 and rotation speed of 500rpm-800rpm, and pause the ball milling for 10min-40min every 0.4h-1h during the ball milling process, and the effective ball milling time is 20h-40h. After ball milling, pass through a 100-mesh sieve to obtain SiBCN amorphous ceramic powder; The molar ratio of the graphite powder to the hexagonal boron nitride powder is 3:(1-2); the molar ratio of the graphite powder to the silicon powder is 3:(1-2); the particle size of the graphite powder is 5.0 μm-10.0 μm, the particle size of the hexagonal boron nitride powder is 0.2 μm-0.6 μm, and the particle size of the silicon powder is 5.0 μm-10.0 μm; 3. Mixed raw materials: At a rotation speed of 250 rpm to 350 rpm, SiBCN amorphous ceramic powder, MAS phase, short carbon fiber with cracked carbon coating and anhydrous ethanol are wet-mixed by ball milling for 8 h to 12 h, and then ultrasonically vibrated for 20 min to 40 min at an ultrasonic power of 400 W to 600 W, and finally the solvent is evaporated at a temperature of 80 ° C to 100 ° C to obtain a mixed raw material; The MAS phase is composed of MgO, Al2O3 and SiO2, and the molar ratio of MgO to Al2O3 is 1:(1-2); the molar ratio of MgO to SiO2 is 1:(2-3); the volume ratio of the anhydrous ethanol to the total mass of the SiBCN amorphous ceramic powder, the MAS phase and the chopped carbon fibers with a cracked carbon coating is (3-5) mL:1 g; the mass percentage of the MAS phase in the mixed raw material is 3%-10%; the volume percentage of the chopped carbon fibers with a cracked carbon coating in the mixed raw material is 10%; 4. Sintering: Under the condition of pre-pressing pressure of 20MPa to 30MPa, the mixed raw materials are pre-pressed for 10min to 30min, and then in nitrogen atmosphere with vacuum degree of 0.9×10 -5 Pa~1.0×10 -5 Pa and a heating rate of 2°C / min to 5°C / min, the temperature was raised to 1600°C to 1800°C, and the vacuum was 0.9×10 -5 Pa~1.0×10 -5 Under the conditions of 50MPa-80MPa sintering pressure and 1600-1800°C temperature, the temperature is kept at 30-60min, and after sintering, the temperature is cooled to room temperature at a cooling rate of 2°C / min-5°C / min to obtain a high-temperature ablation-resistant short carbon fiber reinforced SiBCN-MAS composite material.
2. The method for preparing a high temperature ablation resistant short carbon fiber reinforced SiBCN-MAS composite material according to claim 1, characterized in that The chopped carbon fiber described in step 1 is the chopped carbon fiber after degumming treatment, and the degumming treatment is carried out according to the following steps: placing the chopped carbon fiber in an acetone solution for ultrasonic vibration for 10 minutes to 30 minutes, and finally filtering it out with a sieve and drying it naturally.
Citation Information
Patent Citations
Carbon / carbon fiber-silicon, boron, carbon and nitrogen ceramic composite material and preparation method thereof
CN103626512A
BN-MAS ceramic composite material and preparation method therefore
CN103819180A